2011
DOI: 10.1111/j.1601-183x.2011.00722.x
|View full text |Cite
|
Sign up to set email alerts
|

Neuregulin 3does not confer risk for schizophrenia and smooth pursuit eye movement abnormality in a Korean population

Abstract: Located on chromosome 10q22-q23, the human neuregulin3 (NRG3) is considered to be a strong positional and functional candidate gene for schizophrenia pathogenesis. Several case-control studies examining the association of polymorphisms in NRG3 with schizophrenia and/or related traits such as delusion have been reported recently in cohorts of Han Chinese, Ashkenazi Jews, Australians and white Americans of Western European ancestry. Thus, this study aimed to comprehensively investigate the association of NRG3 ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 17 publications
1
1
0
Order By: Relevance
“…A study of NRG1 genotypes with eye movement deficits in 113 patients with schizophrenia and 106 age-matched healthy controls found no relationship between NRG1 genotype (SNP8NRG222662, SNP8NRG243177) and ASEM or SPEM task performance ( Haraldsson et al, 2010 ). Consistent with Haraldsson’s study, two studies in Korea also found no associations between NRG1 (rs35753505G, rs4623364G; rs6994992T rs3924999A) and ASEM or SPEM abnormality ( Pasaje et al, 2011 ; Kim et al, 2012 ). However, the result in healthy subjects showed interaction between NRG1 and eye movement deficits.…”
Section: Introductionsupporting
confidence: 81%
“…A study of NRG1 genotypes with eye movement deficits in 113 patients with schizophrenia and 106 age-matched healthy controls found no relationship between NRG1 genotype (SNP8NRG222662, SNP8NRG243177) and ASEM or SPEM task performance ( Haraldsson et al, 2010 ). Consistent with Haraldsson’s study, two studies in Korea also found no associations between NRG1 (rs35753505G, rs4623364G; rs6994992T rs3924999A) and ASEM or SPEM abnormality ( Pasaje et al, 2011 ; Kim et al, 2012 ). However, the result in healthy subjects showed interaction between NRG1 and eye movement deficits.…”
Section: Introductionsupporting
confidence: 81%
“…These SNPs however were not in LD with any other reported SNPs in terms of r 2 (see Figure 5 for pairwise LD information in Caucasians on these and all other SNPs mentioned in this review and shown in Figure 1). Two more positive studies reported an association between rs10883866 and/or correlated SNPs and schizophrenia, [Kao et al, 2010] and [Morar et al, 2011], There have also been three negative studies [Zhang et al, 2013; Pasaje et al, 2011; Chen et al, 2009] and the genomic region does not show significant signals in the biggest genome wide association study for schizophrenia to date of 150,00 samples [Schizophrenia Working Group of the Psychiatric Genomics Consortium, 2014]. Therefore, the involvement of these variants with risk for schizophrenia remains in question.…”
Section: Neuregulin 3 Associations With Schizophreniamentioning
confidence: 99%